Effects of technology breaks on media multitasking with college students. (4th May 2018) - Guinness, Kendra E.; Beaulieu, Lauren; MacDonald, Jacquelyn M.
Abstract : Media multitasking involves alternating between completing academic tasks and using technology for nonacademic purposes. We evaluated the effects of technology breaks on media multitasking during independent study with 2 undergraduate students. The intervention involved teaching participants to implement noncontingent technology breaks. Participants were instructed that they could check their text messages, e‐mails, or social media during technology breaks. The initial schedule of breaks was determined by the participants' media multitasking during baseline, and the schedule of breaks was gradually thinned. The results showed that the technology breaks decreased media multitasking for both participants despite there being no programmed consequences for media multitasking. Additionally, the participants implemented the technology breaks with a high level of fidelity. Our findings demonstrate the utility of an antecedent‐based self‐management strategy at decreasing media multitasking with college students.